Влияние фракции до 5 кДа из мозга холодоадаптированных рыб на жизнеспособность карася серебряного в условиях холодового стресса - Гулевский, А.К.; Грищенко, В.И.; Релина, Л.И.; Грищенкова, Е.А.; Погожих, Е.Г.; Сысоева, И.В.; Сысоев, А.А. (Видавничий дім "Академперіодика" НАН України, 2009)
Дослiджено вплив фракцiї до 5 кДа з мозку холодоадаптованого карася срiбного Carassius auratus на життєздатнiсть та енергетичнi параметри у риб при холодовому стресi влiтку. Показано, що експозицiя при 5–6 ºС влiтку призводить до загибелi риб на 3-тю 5-ту добу i до iстотного зниження активностi ЛДГ, а також до пiдвищення вмiсту лактату та пiрувату. Встановлено, що фракцiя до 5 кДа забезпечує виживанiсть риб пiд час холодової аклiмацiї влiтку протягом 9 дiб, сприяє зниженню рiвня АТФ, а також нормалiзацiї активностi ЛДГ i кiлькостi лактату та пiрувату. The data on the influence of the fraction less than 5 kD from brain of the cold-adapted goldfish Carassius auratus upon viability and energetic indices in the fish during cold stress in summer are presented. Exposure at 5–6 ºС in summer resulted in death of the fish on the 3rd-5th day and in a significant drop in the LDH activity, as well as in an increase in lactate and pyruvate contents. It has been shown that the fraction less than 5 kD provided the survival of the fish during the cold acclimation in summer up to 9 days and promoted a reduction in the ATP level, as well as changes in the LDH activity and lactate and pyruvate quantities towards the normalization of these parameters.